Birth control knowledge among freshmen of four Italian universities - Cegolon, L. (Sci Rep, 2020)
Since sexual health education (SHE) is not mandatory in Italian schools, we conducted a survey on freshmen of four Italian university campuses in 2012 to investigate the respective level of sexual health knowledge (SHK) in relation to birth control, with the aim to inform public health policy makers. A convenience strategy was employed to sample 4,552 freshmen registered with various undergraduate courses at four Italian universities: Padua university (Veneto Region); university of Milan (Lombardy Region); university of Bergamo (Lombardy Region); university of Palermo (Sicily Region). We investigated the level of SHK on birth control using 6 proxy indicators: (1) the average length of a woman’s period [outcome with 3 levels: wrong (base) vs. acceptable vs. correct]; (2) the most fertile interval within a woman’s period (binary outcome: correct vs. wrong answer); (3) the event between the end of a period and the beginning of the next cycle (binary outcome: correct vs. wrong answer); (4) the average survival of spermatozoa in the womb (binary outcome: correct vs. wrong answer); (5) the concept of contraception (binary outcome: correct vs. wrong answer); (6) the efficacy of various contraceptives to prevent unintended pregnancies (linear score: 0–17). We fitted 6 separate models of multiple regression: multinomial for outcome 1; logistic for outcomes 2, 3, 4, 6; linear for outcome 6. Statistical estimates were adjusted for a number of socio-demographic factors. Results were expressed as odds ratios (OR) for the 4 multiple logistic regression models, linear coefficients (RC) for the linear regression model and relative risk ratio (RRR) for the multinomial logistic regression model. The level of significance of each risk estimate was set at 0.05. The level of SHK of freshmen sampled was rather low, as 60% interviewees did not know the average length of a woman’s period, the average survival of spermatozoa in the womb and the concept of contraception, whilst the most fertile interval within a woman’s period was known only to 55% of interviewees. The mean score of SHK on the efficacy of various contraceptive methods was only 5 (scale 0–17). Some categories of students were consistently and significantly less knowledgeable on birth control at multivariable analysis: males; students from the university of Palermo; those with vocational secondary school education and those not in a romantic relationship at the time the survey was conducted. The results of this survey clearly call for the introduction of SHE programs in Italian schools, as already done in several European countries. School SHE should start as early as possible, ideally even before secondary school. SHE should be holistic and delivered with a multiple agency coordinated approach involving the Ministry of Health, the Ministry of Education, University and Scientific Research (MIUR), families, schools, public health departments, primary health care providers, pharmacists, media, other.